2017
DOI: 10.3892/ol.2017.7148
|View full text |Cite
|
Sign up to set email alerts
|

L‑type amino acid transporter 1 expression is upregulated and associated with cellular proliferation in colorectal cancer

Abstract: Abstract.Previous studies have shown that the L-type amino acid transporter 1 (LAT1) is highly expressed in many types of cancer. Upregulated LAT1 expression is considered to be associated with cancer cell proliferation. In the present study, we investigated LAT1 expression in 210 patients with colorectal cancer (CRC) and 40 patients with colonic adenoma using an immunohistochemical method, and analyzed the associations between LAT1 expression and clinicopathological factors and prognosis. The biological signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…[ 38,39 ] Specifically, LAT‐1 plays a key role to supply EAA to growing tumor cells by activating progrowth signaling pathways such as the mammalian target of rapamycin (mTOR). [ 40 ] To examine whether if uptake of Nano‐pPAAM could be mediated via LAT‐1, we attempted to block its intracellular entry by using the LAT‐1 inhibitor, 2‐amino‐2‐norbornanecarboxylic acid (BCH). Inductively coupled plasma mass spectrometry (ICP–MS) was employed to determine the intracellular content of Si in MDA‐MB‐231 cells with and without BCH (10 × 10 −3 m ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 38,39 ] Specifically, LAT‐1 plays a key role to supply EAA to growing tumor cells by activating progrowth signaling pathways such as the mammalian target of rapamycin (mTOR). [ 40 ] To examine whether if uptake of Nano‐pPAAM could be mediated via LAT‐1, we attempted to block its intracellular entry by using the LAT‐1 inhibitor, 2‐amino‐2‐norbornanecarboxylic acid (BCH). Inductively coupled plasma mass spectrometry (ICP–MS) was employed to determine the intracellular content of Si in MDA‐MB‐231 cells with and without BCH (10 × 10 −3 m ).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids are indispensable for the proliferation of cancer cells, and transported to the cell by a selective transporter on the plasma membrane 6 . Several lines of evidence have shown that amino acid transporters are upregulated in cancer cells while supporting large-scale growth and reproduction [7][8][9] . L-type amino acid transporter 1 (LAT1) transports neutral amino acids into cells in a Na + -independent manner 10 .…”
mentioning
confidence: 99%
“…L-type amino acid transporter 1 (LAT1) transports neutral amino acids into cells in a Na + -independent manner 10 . LAT1-mediated leucine uptake interactions with cell growth, transcription, and translation through the mammalian Target of Rapamycin (mTOR) signaling pathway 8,9 . Because many reports have shown that LAT1 is highly expressed in cancer cells, LAT1 has become a novel target for cancers [11][12][13] .…”
mentioning
confidence: 99%
“…16 However, LAT1 is the main L-leucine (L-Leu) transporter expressed in T-cell receptor (TCR)-activated T cells 17 and natural killer cells. 18 The expression of LAT1 is increased in many cancer cells, 19 including malignant skin lesions. 20 LAT1 is the main mediator of L-Leu uptake in malignant cells, and its usefulness as a target to inhibit cancer proliferation has been explored.…”
mentioning
confidence: 99%